Research trend on accountability and government performance: A bibliometric analysis approach - Muhammad Ahyaruddin; Mohd Nor Hakimin bin Yusoff; Siti Afiqah binti Zainuddin; Agustiawan Agustiawan (Journal of Accounting and Investment, 2023)
Research aims: This research aims to analyze the trends, map the conceptual structure, and present the picture of research direction on accountability and government performance topics.Design/Methodology/Approach: A bibliometric analysis was used to obtain a structured overview and the research trend on accountability and government performance domains. The authors used the Scopus database from 1983 to 2022 and got 214 published documents, which were then analyzed with VOSviewer software and “Scopus Analyze Search Results.”Research findings: This study uncovered a significant increasing trend in the number of publications on accountability and government performance research, from two documents in 1985 to eighteen documents in 2022. The USA is the most productive country publishing on accountability and government performance research, followed by the United Kingdom, Indonesia, China, Australia, Canada, Germany, Netherlands, Spain, and Italy. The keywords that can be used for further research related to accountability and government performance are e-government, transparency, local government, governance approach, performance management, and corruption.Theoretical contribution/Originality: Based on the best of the authors’ knowledge, this is the first paper that analyses the research trend on accountability and government performance with the use of bibliometric analysis. In addition, for exploring and analyzing large volumes of scientific research, the use of bibliometric analysis is a popular and rigorous method.Practitioner/Policy implication: The use of bibliometric analysis is essential to identify research gaps and look for themes or terms and become a potential direction to explore the relationship of each term.